Effects of home-based virtual reality upper extremity rehabilitation in persons with chronic stroke: a randomized controlled trial - Hiroyuki Ase; Kaoru Honaga; Mami Tani; Tomokazu Takakura; Futoshi Wada; Yuhei Murakami; Reina Isayama; Akira Tanuma; Toshiyuki Fujiwara (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Upper extremity rehabilitation in persons with stroke should be dose-dependent and task-oriented. Virtual reality (VR) has the potential to be used safely and effectively in home-based rehabilitation. This study aimed to investigate the effects of home-based virtual reality upper extremity rehabilitation in persons with chronic stroke. Methods This was a single-blind, randomized, controlled trial conducted at two centers. The subjects were 14 outpatients with chronic stroke more than 6 months after the onset of the stroke. The participants were randomly divided into two groups. The intervention group (n = 7) performed a home rehabilitation program for the paretic hand (30 min/day, five days/week) using a VR device (RAPAEL Smart Glove™; NEOFECT Co., Yung-in, Korea) for four weeks. The control group (n = 7) participated in a conventional home rehabilitation program at the same frequency. All participants received outpatient occupational therapy once a week during the study period. The outcome measures included the Fugl-Meyer Assessment of upper extremity motor function (FMA-UE), Motor Activity Log-14 (MAL), Jebsen-Taylor Hand Function Test (JTT), and Box and Block Test (BBT) scores. Results All 14 participants completed the study. Compared to the control group, the intervention group showed more significant improvements in FMA-UE (p = 0.027), MAL (p = 0.014), JTT (p = 0.002), and BBT (p = 0.014). No adverse events were observed during or after the intervention. Conclusion Compared to a conventional home program, combining a task-oriented virtual reality home program and outpatient occupational therapy might lead to greater improvements in upper extremity function and the frequency of use of the paretic hand. Trial registration: This study was registered in the University Hospital Medical Information Network (UMIN) Clinical Trial Registry in Japan (Unique Identifier: UMIN000038469) on November 1, 2019; https://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000043836 .